Students’ Perceptions of National Identity at a University While Studying Abroad - CENDANA TRICIA JANUARISTY GULTOM; MUKHAMAD MURDIONO; BUDI MULYONO; IQBAL ARPANNUDIN; RAMADHANI ADITIA TRI HADMAZA (Jurnal Moral Kemasyarakatan, 2026)
This study aims to describe how Indonesian students interpret their national identity while also introducing Indonesian culture during their studies abroad. The study is motivated by the phenomenon that cross-cultural experiences can strengthen, change, or challenge students’ understanding of their Indonesian identity. The method used is descriptive qualitative research with a phenomenological approach. The study involved five students from a university participating in student exchange and international internship programs in South Korea, Germany, and Thailand. Data were collected through in-depth interviews and analyzed using the Miles and Huberman interactive model. The results indicate that national identity is shaped through reflection, social interaction, and cultural exposure in daily life. The students promoted Indonesian culture through moral values, good manners, and professionalism to counter negative stereotypes; by consistently upholding their principles amid cultural differences; and by introducing the Indonesian language, batik, and cuisine. International experiences were found to strengthen national identity through cultural diplomacy, moral awareness, and a sense of responsibility as representatives of the nation.